Koncept „szczęście” w językowym obrazie świata Polaków i Rosjan. Аspekt diachroniczny (paremiologiczny) i synchroniczny (asocjacyjny) - Rodziewicz, Barbara (Studia Rossica Posnaniensia, 2010)
The article shows the realization of the concept of happiness as a unit of the axiological system in Polish and Russian paremiology and in the newest associatable dictionaries. Verbalization of the concept of happiness, in both proverbs and sayings, as well as in linguistic awareness of contemporary Polish and Russian people, mirrors the ideas about basic and desired existential values as an integral part of the culture and the concept of the ideal of a unit, a social group and the whole nation.